Anomalous Origin of the Vertebral Artery - Shinohara, André Luis (2018)
Introduction  The present article presents a rare case of variation of the left vertebral artery, which originated from the aortic arch, between the common carotid artery and the subclavian artery, although classic descriptions of the vertebral artery indicate its origin at the subclavian artery, where it penetrates the foramen transverse and ascends cervically to the foramen magnum. Case presentation  The anatomical peculiarity of the vertebral artery is evidenced. The origin of the vertebral artery was identified directly from the aortic arch in a dissected human specimen. Conclusion  In view of the numerous surgical procedures performed in this area, the clear understanding of its topographic layout is indispensable, and might change surgical procedures performed in the region.